Efficacy and Safety of Remimazolam Tosilate Combined With Esketamine for Analgesic Sedation in Mechanically Ventilated ICU Patients: A Single-Arm Clinical Study Protocol - Song, Xuan; Wang, Feng; Dong, Ranran; Zhu, Kehan; Wang, Chunting (Frontiers in Medicine, 2022)
Introduction: Patients in the intensive care unit (ICU) frequently experience increased heart rate, blood pressure, and respiration rate as a product of anxiety and restlessness about their condition and treatments. Analgesia and sedation commonly involve benzodiazepines or opioids that lead to respiratory suppression and other adverse reactions. Remimazolam tosilate is a short-acting GABAA receptor agonist with reduced cardiovascular and respiratory inhibition compared to other commonly used benzodiazepines. Esketamine is a non-competitive N-methyl-D-aspartic acid (NMDA) receptor inhibitor that inhibits hyperalgesia and prolongs postoperative analgesia. It also reduces postoperative pain, delirium, and the use and acute tolerance of opioids. This study aims to assess the efficacy and safety of remimazolam tosilate combined with esketamine and sufentanil for sedation and analgesia in mechanically ventilated ICU patients. Methods:This prospective, single-arm, single-center, open-label clinical trial will be conducted from January 2022 to December 2023. The study will include 200 adult patients (≥18 years) from Shandong Provincial Hospital (affiliated with Shandong First Medical University) who are mechanically ventilated and admitted to the ICU between 24 and 72 hours from the time of ventilation and who are administered analgesia and sedatives. Patients will undergo arterial blood gas analysis before administration. Remimazolam tosilate (0.2 mg/kg) will be injected intravenously within 30 seconds, followed by continuous infusion at a rate of 0.1 to 0.3 mg/kg/h via micropump. Esketamine (0.25 mg/kg) will be injected intravenously and maintained at 0.15 mg/kg/h, while sufentanil will be maintained at the rate of 0.1 to 0.2 µg/kg/h. The primary study outcome is the overall time required to maintain sedation. Secondary outcomes will include the total dosage used to reach the target sedation level, total mechanical ventilation time, awakening time, length of hospital stay, and incidence of cardiorespiratory-related adverse events and delirium. Adverse events (AEs) will be reported regardless of their relationship to the experimental drugs. AEs associated with adverse drug reactions will be classified as "affirmative correlation," "possible relevance," and "unable to determine." A paired t-test or Wilcoxon signed-rank test will be used to compare the changes of observed indexes before and after treatment. A P < .05 will be considered statistically significant.